We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
166
2
avatar+160 

If in a triangle ABC, ab = c2  prove that

                cos(A - B) + cos C + cos 2C = 1

 

NB - could only solve if a and b are equal to c [equilateal]...but not sure if correct reasoning.

Hope you are having a good day...regards 

 May 26, 2019
edited by OldTimer  May 26, 2019
edited by OldTimer  May 26, 2019
 #1
avatar+67 
+3

From the sine rule \(\displaystyle \frac{a}{\sin(A)}=\frac{b}{\sin(B)}=\frac{c}{\sin(C)},\)

we can say that 

\(\displaystyle \frac{ab}{\sin(A)\sin(B)}=\frac{c^{2}}{\sin^{2}(C)},\)

and since we are told that \(\displaystyle ab=c^{2},\)

it follows that 

\(\displaystyle \sin(A)\sin(B)=\sin^{2}(C) \dots(1)\)

 

Expanding the LHS of the (supposed) identity using standard trig identities, we have

 

\(\displaystyle \cos(A)\cos(B)+\sin(A)\sin(B)+\cos(C)+1-2\sin^{2}(C)\)

 

which equals, (making use of (1)),

 

\(\displaystyle \cos(A)\cos(B)-\sin(A)\sin(B)+\cos(C)+1\)

\(\displaystyle =\cos(A+B)+\cos(C)+1\)

\(\displaystyle =\cos(180-C)+\cos(C)+1\)

\(\displaystyle =-\cos(C)+\cos(C)+1 \)

\(\displaystyle =1.\)

.
 May 27, 2019
 #2
avatar+160 
+1

Thanks that was great Tiggsy!!!

 May 28, 2019

16 Online Users

avatar